Gut microbiota structure of rats under introduction of the diet shredded xenograft substrate - P’yatnytskyi, Yu; Pokryshko, O (Annals of Mechnikov’s Institute, 2020)
The data about the influence of lyophilized xenograf powder on rats small intestines and colons cavities microflora composition at the standard conditions and are presented in this article. After feeding animals by this powder for 90 days the disappearance of Klebsiella spp., Proteus spp., S. aureus populations, the reducing of a colonization density of the intestine by other lactosonegative species of Enterobacteriaceae, Bifidobacteria and Candida and increased quantitative indicators specific to populations of E. coli and Clostridia are noted. However, the adding to the rats ration this substrate did not significantly affect the microbiota of different parts of the digestive tract.